Impact of dedicated outpatient pulmonary follow‐up for hospitalized patients with acute pulmonary embolism. (20th January 2022) - Noto, Joseph G.; Rali, Parth
Abstract: Pulmonary embolism (PE) response teams are the standard of care for the management of acute PE. The complications of PE extend far beyond the initial hospitalization period. In this study, we examined the role and potential benefits of dedicated pulmonary follow‐up after hospital discharge for patients with PE.